Development and assessment of engineering project management competences in the context of Project-Based Learning (PBL) - Souza, Mariane C. (2019)
The International Association of Project Management (IPMA) has defined the Individual Competency Baseline (ICB) as a three-dimensional competency structure that the project management professional must develop: competences focused on practice, people, and perspectives. The ICB presents as an example the following approaches to developing competences: self-development, peer development, teaching and training, mentoring, and through simulation and games. Some of these examples are related to active learning, which enables greater autonomy of the student, stimulation of creativity, encouragement of communication and teamwork with frequent feedback from the teacher. In the Masters of Engineering Project Management of the University of Minho, Portugal, there are two courses focused on the development and assessment of competences focused on people, designed to provide moments of active learning. This paper aims to analyse how these courses have contributed to the development and assessment of people-focused competences through Project-Based Learning (PBL) and portfolios. This study is based on a documentary analysis of 70 portfolios of one academic year of the two courses, and a focus group of 10 students, in order to understand their perception about the impact of different teaching-learning moments. The results showed that the development of competences has been more enriching for the students, when compared to learning more centred in the teacher than in the student. The specificity to develop and create the activities (development of an individual portfolio) was proven in the study, as well as projects with real contexts are fundamental for the development of personal competences, being the most outstanding teamwork, communication, conflict management and interpersonal relationship. Finally, the results show that the development and assessment of competences with teaching strategies using active learning instigates the student to discuss and make practical the prese